Reconstruction of Vesicle Assemblies with DNA Nanorulers for Resolving Heterogeneity of Vesicles in Live Cells - Zhang, Yueyue (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.